Effect of sacubitril–valsartan on left ventricular remodeling in patients with acute myocardial infarction after primary percutaneous coronary intervention: a systematic review and meta-analysis - Liu, Yiheng; Sun, Yue; Dai, Weiran (Frontiers in Pharmacology, 2024)
Background: Sacubitril-valsartan has been widely reported for reducing the risk of cardiovascular death and improving left ventricular remodeling in patients with heart failure (HF). However, the effect of sacubitril-valsartan in patients with acute myocardial infraction (AMI) remains controversial. Therefore, we conducted this meta-analysis to investigate whether sacubitril-valsartan could reverse left ventricular remodeling and reduce cardiovascular adverse events in AMI patients after PPCI.: Two researchers independently retrieved the relevant literatures from PubMed, Embase, The Cochrane Library, China National Knowledge Infrastructure (CNKI) and Wanfang database. The retrieval time was limited from inception to 1 June 2023. Randomized controlled trials (RCTs) meeting the inclusion criteria were included and analyzed. Results: Totally, 21 RCTs involving 2442 AMI patients who underwent PPCI for revascularization were included in the current meta-analysis. The meta-analysis showed that compared with ACEI/ARB group, sacubitril-valsartan treatment in AMI patients after PPCI significantly reduced left ventricular end-diastolic dimension (LVEDD) (WMD -3.11, 95%CI: -4.05~-2.16, P<0.001), left ventricular end-diastolic volume (LVEDV) (WMD -7.76, 95%CI: -12.24~-3.27, P=0.001), left ventricular end-systolic volume (LVESV) (WMD -6.80, 95%CI: -9.45~-4.15, P<0.001) and left ventricular end-systolic dimension (LVESD) (WMD -2.53, 95%CI: -5.30~0.24, P<0.001). Subgroup analysis according to the dose of sacubitril-valsartan has the similar result. Meanwhile, PPCI patients using sacubitril-valsartan therapy showed lower risk of MACE (OR=0.36, 95%CI: 0.28~0.46, P<0.001), myocardial reinfarction (OR=0.54, 95%CI: 0.30~0.98, P=0.041) and HF (OR=0.35, 95%CI: 0.26~0.47, P<0.001) without increasing the risk of renal insufficiency, hyperkalemia and symptomatic hypotension. At the same time, the change of LV ejection fraction (LVEF) (WMD 3.91, 95%CI: 3.41~4.41, P<0.001) , 6 min walk test (6MWT) (WMD 43.56, 95%CI: 29.37~57.76, P<0.001) and NT-proBNP level (WMD -130.27, 95%CI:-159.14~-101.40, P<0.001) were statistically significant.In conclusion, our meta-analysis indicates that compared with ACEI/ARB, sacubitril-valsartan may be superior to reverse left ventricular remodeling, improve cardiac function and effectively reduce the risk of MACE, myocardial reinfarction and HF in AMI patients after PPCI during follow-up without increasing the risk of adverse reactions including renal insufficiency, hyperkalemia and symptomatic hypotension.